Et brev fra Rønnebæksholm af 22. november 1847 - Pedersen, Kim Arne (Grundtvig-studier, 2010)
Et brev fra Rønnebæksholm a f 22. november 1847[A letter from Rønnebæksholm, 22 November 1847]By Kim Arne PedersenA hitherto unpublished letter dated 22 November 1847 written to Grundtvig by Marie Toft (his future second wife) is chiefly concerned with the efforts of Grundtvig to gain royal assent to the publication of a further edition of Kirke-Psalmer udgivne til Prøve a f Kjøbenhavns geistlige Convents Psalme-Comitee [Church hymns issued for trial by the Hymn-Committee of the Clerical Convention of Copenhagen], commonly called, as here, Prøveheftet [The trial booklet, or specimen volume]. Grundtvig was a member of the committee and a major contributor to the compilation. In the event, the King (Christian VIII) withheld his assent for want of evidence that the Prøveheft had won sufficiently wide acceptance, and the Convention ultimately rejected the Committee’s work. However, Toft’s letter confirms the presumption that Grundtvig could by now mobilise ready personal support from a network of individuals and congregations of a Grundtvigian persuasion. He was by now a unifying figure among them and generally accepted as their leader.